2019
DOI: 10.1186/s13024-019-0325-5
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging Biomarkers for Alzheimer’s Disease

Abstract: Currently, over five million Americans suffer with Alzheimer’s disease (AD). In the absence of a cure, this number could increase to 13.8 million by 2050. A critical goal of biomedical research is to establish indicators of AD during the preclinical stage (i.e. biomarkers) allowing for early diagnosis and intervention. Numerous advances have been made in developing biomarkers for AD using neuroimaging approaches. These approaches offer tremendous versatility in terms of targeting distinct age-related and patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
137
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(141 citation statements)
references
References 189 publications
(202 reference statements)
3
137
0
1
Order By: Relevance
“…Pathological tau deposition represents another key biomarker of AD [ 45 , 46 ]. The development of selective tau tracers, such as the most extensively used tracer 18 F-Flortaucipir [ 47 ], allows researchers to investigate regional distribution of tau pathology in the living human brain [ 46 , 48 , 49 ]. In the preclinical stage, the relationship between the symptoms of SCD and tau burden has been reported by Swinford and colleagues [ 50 ].…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…Pathological tau deposition represents another key biomarker of AD [ 45 , 46 ]. The development of selective tau tracers, such as the most extensively used tracer 18 F-Flortaucipir [ 47 ], allows researchers to investigate regional distribution of tau pathology in the living human brain [ 46 , 48 , 49 ]. In the preclinical stage, the relationship between the symptoms of SCD and tau burden has been reported by Swinford and colleagues [ 50 ].…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…Studies ( Kuhl et al, 1982 ) have demonstrated that in older ages cerebral glucose metabolism decreases, and that the MTLs, the posterior cingulate cortex and the precuneus show the least age-dependent change. These regions express significant hypometabolism in AD ( Márquez and Yassa, 2019 ), and Mosconi et al (2008) showed that FDG-PET could be used to differentiate healthy subjects from AD patients with 98 to 99% specificity. Recent work by ADNI 2 PET Core has examined how FDG-PET and amyloid PET can be combined to track progression of AD.…”
Section: Ad Biomarkers – Type and Definitionmentioning
confidence: 99%
“…Using other methods to diagnose the different types of dementia will require neuroimaging technology progress, such as positron emission tomography (PET) and magnetic resonance imaging [42]. The different imaging model not only provides complementary information but also the spatial distribution of the measured value can provide abundant information [43]. To some extent, the development of detection technology has broadened the range of biomarkers.…”
Section: Biomarkers Of Admentioning
confidence: 99%
“…The National Institute on Aging 2018 Alzheimer's Disease Research Summit "road to treatment and prevention" made an important recommendation to carry out precision medical research in the field of AD. The integration of artificial intelligence and neuroimaging data with other omics data will be the key to progress in the field of AD treatment [43]. In addition to biological factors (such as genetics, CSF and blood proteomics) and AD medical risk factors (such as hypertension, diabetes, obesity, and depression), we can also focus on national factors that may be related to the onset, diagnosis time between different ethnic groups, clinical manifestations and differences between AD [54].…”
Section: Biomarkers Of Admentioning
confidence: 99%